Procedures And Strategies For Translating Of Religious Cultural Terms From Persian Into English - Ebrahimi, Mehri (2019)
Persian literature has had a significant role in introducing Middle Eastern culture and art to the West. Studies undertaken on the translation of Persian literature have been mostly focused on the Persian classical poetry while modern Persian literature, especially non-fiction literature has been ignored. Translation of modern non-fiction Persian literature with Islamic content has grown drastically in the post-revolutionary period. Therefore, this study is based on three books in the field of non-fiction modern Persian literature titled Lost in the Crowd, Hajj, and Shi'ite Islam. The selected texts contain various Islamic terms common in Persian Middle Eastern religious context which bear highly culture-loaded meanings. This research has two phases. In the first phase, the study draws upon Toury’s (2012) methodology of descriptive translation studies (DTS). The study attempts to identify various types of Islamic terms and then identifies the translation procedures and overall strategies used in their translation in order to uncover norms which govern the translation process in the translation of Islamic religious cultural terms from Persian into English. AlGhamdi’s (2016) taxonomy for the recognition of types of Islamic terms and Vinay and Darbelnet’s (1995) and Mansor’s (2011) models were applied to show translation procedures. In addition, Venuti’s (2000) two translation strategies were selected in order to reveal the overall translation strategy in this study. The result yielded 1160 cases of Islamic religious cultural terms in 13 categories and the use of 17 different procedures in the process of translating.